Loserthink : How untrained brains are ruining the world - Adams, Scott (Portfolio/Penguin, 2019)
"No matter how smart or well-informed you are, you're probably trapped in a mental prison without knowing it. Scott Adams, the world-famous creator of Dilbert and New York Times bestselling author of Win Bigly, teaches us how to recognize and avoid the "loserthink" that prevents us from seeing outside our own bubbles of reality"--